ARCA PERUNGGU GARUDA DAN BODDHISATVA PADMAPANI DARI PADANGLAWAS - Ery Soedewo (Balai Arkeologi Sumatera Utara, 2006)
Padang Lawas is one of some sites from Hindoo-Buddhist period inNorth Sumatra. Based on artefactual data, many archaeologists agreedthat religion background of Padang Lawas antiquities is Vajrayana orTantrayana Buddhism. It‟s supported by the new discoveries of twobronze sculptures from Candi/Biara Tandihat site, i.e. Garuda andBoddhisatva Padmapani. Now these sculptures are collected inMuseum Negeri Sumatera Utara, Medan